2011
DOI: 10.1016/j.foreco.2011.06.043
|View full text |Cite
|
Sign up to set email alerts
|

Can we use shelterwoods in Mediterranean pine forests to promote oak seedling development?

Abstract: International audienceThe use of shelterwoods to favour the development of natural or underplanted seedlings is common in temperate forests but rare in the pine forests of the Mediterranean area. Our aim was to assess the use of shelterwoods in Aleppo pine (Pinus halepensis) woodlands in southern France to promote the survival and growth of two co-occurring oak species: the deciduous Quercus pubescens and the evergreen Quercus ilex. Twelve Aleppo pine stands were selected and differentially thinned to create a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 47 publications
(47 reference statements)
1
17
0
7
Order By: Relevance
“…In a Pinus halepensis Mill. shelterwood in southern France, Prévosto et al (2011a) found that the growth of sown Q. ilex was higher in the stands with lower BA (10 m 2 ha -1 ). We observed an important increase in the height of Q. ilex regeneration in the years immediately after the canopy opening, whereas in the pine plantation no evidences of a clear height increase were found during the same period of time.…”
Section: Discussionmentioning
confidence: 90%
“…In a Pinus halepensis Mill. shelterwood in southern France, Prévosto et al (2011a) found that the growth of sown Q. ilex was higher in the stands with lower BA (10 m 2 ha -1 ). We observed an important increase in the height of Q. ilex regeneration in the years immediately after the canopy opening, whereas in the pine plantation no evidences of a clear height increase were found during the same period of time.…”
Section: Discussionmentioning
confidence: 90%
“…However, it does not support the hypothesis, derived from f ield studies with seedlings in Mediterranean-type 210 J. Rodriguez-Calcerrada et al / Forest Systems (2013) 22(2), 202-213 habitats (Valladares and Pearcy, 2002;Rodríguez-Calcerrada et al, 2010b;Prévosto et al, 2011), that increasing shade would exacerbate sensitivity to increased drought. One explanation for this result is that we studied large, mature saplings well established in the understory.…”
Section: Performance Of Common Box After a Long-term Reduction In Thrmentioning
confidence: 90%
“…The results confirm the viability of Quercus ilex direct seeding in forest restoration and document predation as a major current limitation in Mediterranean environments in the absence of protection. Partial shading/ shelter appears to have a major influence on acorn early survival and growth (Pausas et al, 2004;Rodríguez-Calcerrada et al, 2008;Prévosto et al, 2011b). Micromammal and rabbit activity was evident and dramatic all over the study site.…”
Section: Discussionmentioning
confidence: 94%